A Quality Improvement Initiative to Reduce Opioid Consumption after Cesarean Birth. Issue 5 (September 2019) - Burgess, Adriane; Harris, Amy; Wheeling, Julia; Dermo, Roni
Abstract: Background: One in 300 opioid naïve women become addicted to opiates after cesarean birth. After cesarean, women are often prescribed more opiates at discharge than necessary, resulting in increased opportunity for diversion. Purpose: To improve use of comfort strategies and nonopioid medications to decrease the amount of opioids required postoperatively and prescribed at discharge, in women who gave birth via cesarean. Methods: An interdisciplinary workgroup was convened to assess data on opioid use, prescribing practices at discharge, and nurses' use of alternative comfort strategies from January to March 2018. A comfort bundle was designed to include standardized use of preoperative acetaminophen, postoperative comfort education, simethicone, postoperative gum chewing, and abdominal binders. Nurses and healthcare providers were educated on the initiative. Data were reevaluated and compared with preintervention data assessing for improvement and adherence to the bundle components. Results: There was a 61% reduction in morphine milliequivalents given to women after cesarean birth between the first quarter in 2018 and the fourth quarter in 2018. Comparing March with December, 2018 data, adherence to each bundle component improved. The percentage of women receiving less than 20 tabs of oxycodone at discharge increased from 26.3% to 96.7%. Implications for Nursing Practice: Nurses should evaluate comfort options provided after cesarean birth and educate women about use of nonopioid pain relief strategies. A standardized process to address pain and comfort after cesarean birth may decrease exposure to opioids while maintaining comfort. Abstract : Reevaluation of routine prescription of opioids for postoperative pain has been one of the many responses to the opioid crisis in the United States. In this quality improvement project, an interdisciplinary team developed a bundle of nurse-initiated comfort measures to offer additional options for pain relief for women after cesarean birth. Provider order sets and prescribing practices were changed. Data were collected over the first year of the project. Opioid use during hospitalization and the amount prescribed at discharge decreased while patient satisfaction improved. Pain relief options as adjuncts to medication can be successfully integrated into clinical practice.